HUBUNGAN ANTARA INDEKS PRESTASI DENGAN PENAMPILAN KERJA PERAWAT LULUSAN AKPER PAMENANG PARE DI RSUD. PARE KEDIRI - Nugroho, Christianto (Akademi Keperawatan Pamenang, 2010)
The nurse job performance influenced by many factors, one of them is prestation indeks. PrestationIndeks consit of general lecture, nursing basic lecture, and profesion lecture indeks.These are indicated theirability about nursing science. But Nurse performance has not evaluated well. This research was aimed toinvestigate the influence prestation indeks to nurse job performance in Pare hospital.Design used in this research was cross sectional study. The samples are nurses in Pare Hospital, whograduated from Akper Pamenang. These are 44 respondens, selected with total sampling. The data collected byquisioner and observation then analyzed with SPSS Linier Regretion with Significan level p < 0,05.Results showed that general lecture prestation indeks had corelation with nurse job performance(p=0,005), profession basic lecture prestation indeks had corelation with nurse job performance (p=0.004),profession lecture indeks had corelation with nurse job performance (p=0,003) and comulatif prestation indekshad corelation with nurse job performance (p=0,014).It can be concluded that indeks influenced nurse job performance especially general lecture, profesionbasic lecture and profession lecture prestation indeks. So it will recomended to choose higher prestation indeksinnurse recruitment.